The Effect of Online Flight Ticket Discounts Through Traveloka.com on Consumer Satisfaction at Yogyakarta International Airport - Dea Afni Primatari; Irwina Meilani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Selling airplane tickets through E-Commerce is an aviation business that has recently been quite popular among the public. Sales of airplane tickets both domestically and abroad in various E-Commerce show the high level of purchasing airplane tickets. Recently, the growth of E-Commerce, which sells airplane tickets, has been growing rapidly. With the development of E-Commerce, it has made it easier for passengers to buy airplane tickets, one of which is the Traveloka E-Commerce because it is an application that prioritizes ticket and hotel search programs. Apart from that, Traveloka also has unique and interesting original content. This study uses quantitative data. The data used in this study were taken from primary data based on questionnaires distributed to passengers at New Yogyakarta Airport for the time period for conducting the research, namely September 1 - October 31, 2022. With a total of 120 people, the data analysis technique used was Regression Analysis Simple Linear, T Test, F Test and Coefficient of Determination. The results of this study can be concluded that the results of testing the hypothesis using the F-Test to find out whether there is an effect of online airplane ticket discounts through Traveloka.com on passenger satisfaction at the Yogyakarta international airport, from the calculation results of the F-Test shows the value of fcount 0.859008 ftable = 0.575879. It is very clear that H1 is accepted. The magnitude of the influence of discounted online airline tickets through Traveloka.com on the Y variable of passenger satisfaction is known and the correlation value = 0.7722 (Very Strong) and the coefficient of determination is 84% (influence). While the remaining 16% is caused by other factors not examined by researchers.